The effect of local taxes on increasing local original revenue in Bengkulu City - Ariska, Fitriani; Shinta, Seftya Dwi (Privietlab, 2025)
This study analyzes the effect of regional taxes on Regional Own Source Revenue (ROSR) in Bengkulu City and explains the dynamics of ROSR development from 2018 to 2023. Using a quantitative approach, the research employs multiple linear regression with secondary data from regional budget realization reports and regional tax realization by type, covering hotel, restaurant, entertainment, parking, and street lighting taxes. ROSR is treated as an indicator of local fiscal capacity and independence. The results show that hotel, restaurant, and street lighting taxes have a positive and statistically significant effect on ROSR, indicating that hospitality, culinary, and electricity-based tax bases are the dominant contributors to locally generated revenue. In contrast, entertainment and parking taxes do not have a significant effect, reflecting limited sector potential and suboptimal tax administration in these areas. Simultaneously, all five tax types significantly influenced the ROSR, and the model explained a large proportion of its variation, underscoring the importance of regional tax management as an integrated system. The findings highlight the need to strengthen regulations, enhance supervision, expand the formal tax base, and intensify the digitalization of tax collection to optimize the ROSR and support the long-term fiscal independence of Bengkulu City.